Communication in Nuclear Emergency Preparedness: A Closer Look at Information Reception. Issue 11 (11th April 2013) - Perko, Tanja; van Gorp, Baldwin; Turcanu, Catrinel; Thijssen, Peter; Carle, Benny
Abstract : Preparedness of the general population plays a key role in the effective implementation of protective actions in case of a nuclear emergency (e.g., evacuation or intake of iodine tablets). In this context, a good communication of emergency management actors with the public along the entire cycle of preparedness–response–recovery is of paramount importance. This article aims at providing a better understanding of the way people process communicated messages and the factors that may influence how they do this. In particular, it investigates information reception as part of the information processing in precrisis communication. As a case study, the precrisis communication context was chosen, as it has been tackled to a lesser extent in the literature. The empirical data used for this study originated from a large‐scale opinion survey in Belgium. One topic in this survey addressed the information campaign for the distribution of iodine tablets, in the context of preparedness for nuclear emergencies. The findings of this study demonstrate that systematic predictors have a stronger influence on information reception, as compared to heuristic predictors. The latter are only to a minor extent involved in the reception of emergency preparedness information. The hypothesized pattern—that more specific knowledge about the field relates to a higher reception of information—was confirmed for precrisis communication. Contrary to expectations, results showed that people with a high perception of radiation risks were less attentive to information about protective actions. People with little confidence in authorities were also more likely to have a low reception of information.